Uncovering the Roots of Obesity-Based Wage Discrimination: The Role of Job Characteristics - Juan J. Dolado; Airam Guerra (Institute of Labor Economics (IZA), 2021)
This paper investigates the roots of labour market discrimination underlying the negative correlation between body fat percentage and wages. Using a large panel dataset of individuals drawn from the 1997 National Longitudinal Survey of Youth (NLSY97) for the US, we test whether residual wage gaps (once observed differences in productivity related to obesity are controlled for) are due to prejudice (taste-based discrimination) or statistical discrimination. Our main contribution is to examine how these two types of discrimination hinge on a wide range of obese individuals' specific job and occupational characteristics (drawn from the O * Net Online database). Our analysis sheds light on whether discrimination originates from the attitudes of clients, fellow-workers or employers. We find strong empirical evidence supporting taste-based discrimination against obese females, especially as they become older, in jobs requiring frequent communication with either clients or employers. The evidence on this issue for males is weaker. These differences may be explained both by an over-representation of males among employers and different image concerns against people of the same gender.
Keywords: J71; J15; J31; 330; obesity; wages; job characteristics; NLSY97; O*Net Online